IMPLEMENTASI PENILAIAN OTENTIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 KOTA SUKABUMI DALAM PARADIGMA KURIKULUM MERDEKA - Sayyidah Junaidah Al-Bahri; Mulyawan Safwandy Nugraha (JIP: Jurnal Ilmu Pendidikan, 2026)
Authentic assessment is a crucial component of the Merdeka Curriculum, particularly in Islamic Religious Education (PAI), which emphasizes holistic development of students’ attitudes, knowledge, and skills. However, its classroom implementation still encounters practical challenges. This study aims to examine the implementation of authentic assessment in PAI learning at SMP Negeri 1 Kota Sukabumi within the Merdeka Curriculum framework. A qualitative case study design was employed, with data collected through semi-structured interviews, classroom observations, and document analysis involving a PAI teacher as the main informant. Data were analyzed using data reduction, data display, and conclusion drawing, supported by triangulation techniques. The findings reveal that authentic assessment has been implemented through integrated assessment of attitudes, knowledge, and skills using practices, discussions, and observations during the learning process. Teachers provide feedback and follow-up actions; however, limitations remain in the use of written and structured assessment instruments, particularly rubrics. This study underscores the importance of strengthening teachers’ assessment literacy to improve the effectiveness and consistency of authentic assessment in PAI learning.